Analisis Peluang dan Tantangan Kota Subang dalam Kerangka Kawasan Ekonomi Segitiga Rebana - sukandi, Andi (Jurnal Kesehatan & Disiplin Ilmu, 2024)
Abstract The Rebana Triangle Economic Area, which covers the regions of Subang, Majalengka, and Cirebon, has been designated as one of the national strategic areas with the aim of increasing economic growth and infrastructure development in West Java. Subang City, with its strategic position in the middle of the region, has various opportunities and challenges that need to be analyzed to optimize the benefits of this initiative. This research aims to identify and analyze the opportunities and challenges faced by Subang City within the framework of the development of the Rebana Triangle Economic Zone. The research method used includes descriptive qualitative analysis with a literature study approach and in-depth interviews with local stakeholders. The results showed that Subang City has several key opportunities, including increased infrastructure investment, better transportation accessibility with the construction of Patimban Port and the Trans-Java Toll Road, and the potential for industrial and tourism sector development. In addition, the presence of an international industrial park also opens up opportunities for increased employment and local economic growth